2009
DOI: 10.1016/j.brainres.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Impaired blood–brain and blood–spinal cord barriers in mutant SOD1-linked ALS rat

Abstract: Blood-Brain Barrier (BBB) and Blood-Spinal Cord Barrier (BSCB) impairment is an additional accident occurring during the amyotrophic lateral sclerosis (ALS) progression. In this work we aimed to decipher if BBB/BSCB leakage appeared before critical detrimental events and could serve as a marker preceding clinical symptoms. Three different BBB leakage markers: Evans Blue, IgG and hemosiderin, were used to look at the SOD1-linked ALS rat model at presymptomatic and symptomatic stages. Although IgG and hemosideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 37 publications
7
136
1
1
Order By: Relevance
“…In a rat SOD1 model of amyotrophic lateral sclerosis, IgG and hemosiderin were detected in presymptomatic stages, and Evans blue dye extravasation was evident in symptomatic stages. 53 Recent findings in pericyte-deficient mice demonstrated that BBB breakdown causes secondary dendritic damage and neuronal loss. 54 This suggests that accumulation of serum proteins in the AAV-tauP301L model may further contribute to dendritic degeneration.…”
Section: Tau-mediated Neurodegeneration Is Closely Linked To Neurovasmentioning
confidence: 99%
“…In a rat SOD1 model of amyotrophic lateral sclerosis, IgG and hemosiderin were detected in presymptomatic stages, and Evans blue dye extravasation was evident in symptomatic stages. 53 Recent findings in pericyte-deficient mice demonstrated that BBB breakdown causes secondary dendritic damage and neuronal loss. 54 This suggests that accumulation of serum proteins in the AAV-tauP301L model may further contribute to dendritic degeneration.…”
Section: Tau-mediated Neurodegeneration Is Closely Linked To Neurovasmentioning
confidence: 99%
“…The immunohistochemistry analyses were realized using a previously described method [15]. After fixation of the organs in 10% formalin followed by a paraffin-embedding procedure, 7µm-sections were rehydrated, endogenous peroxidases were blocked (0.3% H2O2 in methanol) and non-specific binding antibodies inhibited for 1 hour with 10% goat serum.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Pathophysiology of ALS is poorly understood and likely multifactorial. Proposed starting points for this complex disease targeting the motor neuron population include mitochondrial dysfunction, intracellular protein aggregation, disturbances of RNA metabolism, extracellular toxic environment, impairment at the level of axonal transport and at the neuromuscular synapse (reviewed by [81] ), together with extrinsic events: blood-brain barrier breakdown, glial cell reaction/dysfunction and neuroinflammation [82][83][84][85][86][87][88] . It is known that dying motor neurons influence surrounding cells, of which astrocytes are most commonly investigated.…”
mentioning
confidence: 99%